Comparison of Regulations and The Role of Officials Making Land Deeds In The Reconstruction of Land Registration After Natural Disasters - Sari Ismail, Winda Puspita; Rahaditya, R. (Devotion : Journal of Research and Community Service, 2023)
Indonesia is a country that is on the equator and most of it is a water area. Indonesia is also a country located on the Asian and Australian continents and is directly adjacent to the pacific and indian oceans. So this is what causes Indonesia to be included in the Ring of Fire or Pacific Circle of Fire which is known as a region with many tectonic activities. This legal writing uses normative research methods so that the approach used is a purely normative approach or what is known as normative juridical. This research raises the issue of positive legal provisions of the role of land deed-making officials in the implementation of land registration reconstruction after natural disasters. The implementation of land registration after the natural disaster that occurred on September 28, 2018, Indonesia was hit by an earthquake and tsunami precisely in the Palu area of Central Sulawesi is certainly inseparable from applicable government regulations which are still carried out with various collaborations with other ministries as a form of land registration and provide certainty to legal protection for victims of natural disasters